Gambaran Pengetahuan Remaja Perempuan Tentang Hak Reproduksi Remaja Di Program Studi Kebidanan Fakultas Kedokteran Universitas Airlangga Surabaya - Haida Zahara, - (2020)
Adolescence is a period of transition from children to adults. Reproductive rights are important to know because young people have inadequate knowledge of reproductive rights. The purpose of this study was to determine the description of female adolescent knowledge about reproductive rights in the Midwifery Study Program, Faculty of Medicine, Airlangga University. his research method uses a descriptive design. The population in this study, late adolescents aged 17-21 years, totaled 49 female students in the Midwifery Study Program using total sampling. The instrument used in this study was a questionnaire distributed to adolescents via WhatsApp and e-mail. The questionnaire in this study was adapted from Illustrative Questionnaire for Interview-Surveys with Young People. The results of this study are the primary source of information that is most widely chosen regarding reproductive rights is mothers (42.22%), on the other hand about the process of pregnancy is the teacher in schools (51.02%), and about the relationship between men and women obtained by teachers in schools (34.69%). 89.79% of adolescents know about contraceptive methods and 69.38% know about the source / location of getting contraception. On average, 40.81% of adolescent girls answered correctly about 4 statements regarding pregnancy prevention, treatment for sexually transmitted infections and HIV prevention and care. On average 53.03% of young women answered correctly about 4 statements regarding knowledge about HIV / AIDS. Only 4.08% of respondents do not know the signs and symptoms when a woman is sexually transmitted. On average 47.44% of respondents answered correctly regarding knowledge of protection against HIV. On average 85.71% of respondents supported 3 statements regarding prevention and care support: violence against women. The conclusion in this study is that the source of information most chosen by adolescents is mothers and teachers. Later, The knowledge gained by adolescents can increase knowledge of adolescent reproductive rights.